ONLINE LEARNING THROUGH ZOOM MEETING DURING THE COVID-19 PANDEMIC AT A HIGHER EDUCATION IN SUMEDANG - Sakina, Rahma; Arifin, Riyadh Ahsanul; Wulansari, Devi Indah; Salsabila, Vina Aini (Universitas Suryakancana, 2023)
In the midst of the Covid-19 epidemic, many sectors are affected including education sectors. Teaching-learning activities are commanded to be held online, one of which is through Zoom Meeting application. The purposes of this research are to investigate the perceptions of lecturer and students towards online learning using Zoom meeting, to find out the advantages and disadvantages of online learning through Zoom meetings, and to figure out the students' participation during online learning through Zoom meetings. A descriptive qualitative method is used in this study. To collect the data, some techniques are used involving questionnaire, observation, and semi-structured interview. The questionnaire adapted from Roudlotun Nurul Laili and Muhammad Nasir (2020) and Minhas, et al (2021) was distributed to the fourth semester students and the lecturer of a private university in Sumedang. The findings show that the perceptions of students and lecturer about Zoom Meeting as an online learning application media are very diverse, but this Zoom Meeting application is arguably still effective for online learning. There are some advantages of online learning through Zoom Meeting, such as its flexibility to be used anywhere and on any type of gadget and its beneficial features that make easy for learning activities to take place. Apart from that, there are also disadvantages of using Zoom Meeting as a learning medium. The results show that it wastes a lot of internet data and the internet connection is not stable. The students participate more actively in a smaller scale of class or breakout room than in a large class during online learning.